Transforming US intelligence for irregular war : Task Force 714 in Iraq - Shultz, Richard H., 1947- (Georgetown University Press, 2020)
"Richard H. Shultz examines the pivotal role of intelligence in twenty-first century irregular warfare through an in-depth examination of the fight against Al-Qaeda in Iraq (AQI) between 2004 and 2009. AQI was the most lethal group that fought the US occupation of the country after the toppling of Saddam Hussein. US Special Operations Command deployed Task Force 714, a joint services counterterrorism force, to Iraq to fight the growing insurgency. TF 714's leader, Maj. Gen. Stanley McChrystal, quickly realized that AQI was unlike any insurgent or terrorist organization that preceded it. AQI was comprised of decentralized networks that employed information age technologies to operate across a broad geographical landscape. This book is the story of how TF 714 had to reinvent itself to destroy the leadership, financial units, communications and media centers, intelligence services, bomb production facilities, and arms acquisition procurers of AQI. Along with changes to operational tempo and command structure, TF 714 altered its methods and practices of intelligence collection, analysis, and covert action. TF 714 is an exemplar of successful organizational learning and how intelligence must lead the way in campaigns against nonstate armed groups"--